Stanisław Wyspiański i dawna polska historia - Biołczew, Bojan (Postscriptum Polonistyczne, 2020)
The article draws on a chapter from Boyan Biolchev’s book Stanisław Wyspiański – Encyclopaedist of Neoromanticism (2003). It studies the following contextual aspects of Wyspiański’s plays Bolesław the Brave (Bolesław Śmiały) and Skałka: Wyspiański‘s defining creative relationship with his native Krakow; the playwright’s englobing vision of the two works and intention to stage them as a single play; the historical sources and the literary and historical genesis of the theme of conflict between the king and the bishopsaint; Słowacki‘s influence; critical evaluations of the twoplay cycle.